2013
DOI: 10.1038/ncomms3609
|View full text |Cite
|
Sign up to set email alerts
|

Sox17 is indispensable for acquisition and maintenance of arterial identity

Abstract: The functional diversity of the arterial and venous endothelia is regulated through a complex system of signalling pathways and downstream transcription factors. Here we report that the transcription factor Sox17, which is known as a regulator of endoderm and hemopoietic differentiation, is selectively expressed in arteries, and not in veins, in the mouse embryo and in mouse postnatal retina and adult. Endothelial cell-specific inactivation of Sox17 in the mouse embryo is accompanied by a lack of arterial diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
309
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 264 publications
(337 citation statements)
references
References 55 publications
23
309
3
2
Order By: Relevance
“…We next examined the expression of two downstream Wnt/ β-catenin pathway target genes, Apcdd1 and sex determining region Y-box 17 (Sox17) (40,50), in spinal cords during EAE. In both vascular and nonvascular cells, expression of Apcdd1 mRNA was highly increased by EAE scores 1 and 3 using in situ hybridization with an antisense DIG-labeled probe ( .…”
Section: Resultsmentioning
confidence: 99%
“…We next examined the expression of two downstream Wnt/ β-catenin pathway target genes, Apcdd1 and sex determining region Y-box 17 (Sox17) (40,50), in spinal cords during EAE. In both vascular and nonvascular cells, expression of Apcdd1 mRNA was highly increased by EAE scores 1 and 3 using in situ hybridization with an antisense DIG-labeled probe ( .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated that SOX17 expression during endothelial differentiation is restricted to arteries (Corada et al, 2013;Frame et al, 2015;Matsui et al, 2006). By contrast, SOX7 is expressed from the onset of endothelial differentiation in the yolk sac at E7.5, and is expressed in arterial and venous vasculature (Gandillet et al, 2009;Sakamoto et al, 2007;Zhou et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the embryo proper, in the yolk sac HPCs emerge from a spectrum of endothelial cells in both arterial and venous regions, and in both large and small blood vessels (Frame et al, 2015). As the endothelial expression of SOX17 is restricted to arteries (Corada et al, 2013), this factor cannot control RUNX1 function and EHT in non-arterial vasculatures. Other endothelial transcription factors must therefore be important for regulating HE in the yolk sac.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sox18 is a member of the SoxF family of transcription factors that also includes Sox17 and Sox7 (Dunn et al, 1995). SoxF transcription factors have shown to modulate arteriovenous identity and lymphatic endothelial cell specification (Cermenati et al, 2008;Corada et al, 2013;Francois et al, 2008;Herpers et al, 2008;Pendeville et al, 2008). Previous studies have shown that adult Sox18-/-mice have a defect restricted to zigzag hairs supporting the view that Sox2 and Sox18 have complementing and nonoverlapping functions, driving the formation of different hair types (Pennisi et al, 2000a).…”
Section: Introductionmentioning
confidence: 87%